Linking Competence, Motivation, and Work Discipline to Employee Performance: An Empirical Study of the Regional Development Planning, Research, and Development Agency of Kepulauan Selayar Regency, Indonesia - Ismail, Rezky Yulianty; Laekkeng, Mursalim; Amir, A. (Golden Ratio of Mapping Idea and Literature Format, 2025)
This study aims to determine the influence of Competence, Motivation, and Work Discipline on Employee Performance at the Regional Development Planning, Research, and Development Agency (Bappelitbangda) of Kepulauan Selayar Regency. The research employs a quantitative method, utilizing both primary and secondary data. The sample size for this study consists of 58 respondents. Data processing is conducted using the SPSS analysis tool. The research approach is a quantitative research method. Data were obtained directly from the employees of Bappelitbangda, with a total of 58 respondents, through a questionnaire covering both dependent and independent variables. The data analysis method in this study utilizes a computer-based program, namely SPSS (Statistical Product and Service Solutions). The analyses conducted include descriptive analysis, multiple linear regression analysis, instrument testing (validity and reliability tests), and hypothesis testing (t-test and F-test). The research findings indicate that: (1) Competence has a positive but not significant effect on Employee Performance at Bappelitbangda of Kepulauan Selayar Regency; (2) Motivation has a positive and significant effect on Employee Performance at Bappelitbangda of Kepulauan Selayar Regency; (3) Work Discipline does not have a significant effect on Employee Performance at Bappelitbangda of Kepulauan Selayar Regency.